Diagnoses of alcohol abuse and other neuropsychiatric disorders among house painters compared with house carpenters. - Lundberg, I (1992)
The incidence of alcoholism and the incidence of other neuropsychiatric diagnoses were compared between the 767 house painters and the 1212 house carpenters, born in 1925 or later, who were members of the Stockholm branches of their respective trade unions in 1965 and who had been members for at least 10 years before 1970. Four different outcome registers were used: (1) the alcohol crime register, which contained all persons who had broken any law regulating the handling and consumption of alcohol (follow up period 1972-6). (2) The register of diagnoses at early retirement (follow up period 1971-84). (3) The register of diagnoses at discharge from inpatient psychiatric care (follow up period 1968-83). (4) The register of causes of death (follow up period 1965-86). Exposures to solvents and consumption of alcohol were evaluated by interviews with samples of the cohorts. A high average cumulative exposure to solvents was found among the painters. The mean consumption of alcohol was similar in the two cohorts. The incidence of diagnoses of neuropsychiatric disorders was higher in painters than in carpenters in all registers. Alcoholism was the most common neuropsychiatric disorder diagnosed and showed the highest relative risk. The excess of alcoholism among the painters was, however, due singularly to painters who had several registrations in the alcohol crime register or diagnoses of alcoholism in multiple registers. Thus the study implies that excessive alcohol consumption or severe damage due to alcohol, or both, but not less severe problems, were more common in painters than in carpenters. This suggests an interaction between exposure to solvents and intake of alcohol causing an increase in diagnosis of alcoholism among painters.